2013
DOI: 10.1101/cshperspect.a012609
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Excision Repair in Eukaryotes

Abstract: Nucleotide excision repair (NER) is the main pathway used by mammals to remove bulky DNA lesions such as those formed by UV light, environmental mutagens, and some cancer chemotherapeutic adducts from DNA. Deficiencies in NER are associated with the extremely skin cancer-prone inherited disorder xeroderma pigmentosum. Although the core NER reaction and the factors that execute it have been known for some years, recent studies have led to a much more detailed understanding of the NER mechanism, how NER operates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
670
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 660 publications
(681 citation statements)
references
References 157 publications
9
670
0
2
Order By: Relevance
“…A lesion-bound complex involving at least the TFIIH, XPA, and RPA proteins provide the structural basis to load and properly orient the structure-specific endonucleases ERCC1/ XPF and XPG, which incise, respectively, the damaged strand 5 0 and 3 0 to the lesion. The consequent 25 -30 nucleotide gap is filled in by the replication machinery and sealed by DNA ligases (Moser et al 2007;Ogi et al 2010;Schärer 2013). At the cellular level, TC-NER or GG-NER deficiency results in UV hypersensitivity.…”
Section: The Subpathways Of Nermentioning
confidence: 99%
See 1 more Smart Citation
“…A lesion-bound complex involving at least the TFIIH, XPA, and RPA proteins provide the structural basis to load and properly orient the structure-specific endonucleases ERCC1/ XPF and XPG, which incise, respectively, the damaged strand 5 0 and 3 0 to the lesion. The consequent 25 -30 nucleotide gap is filled in by the replication machinery and sealed by DNA ligases (Moser et al 2007;Ogi et al 2010;Schärer 2013). At the cellular level, TC-NER or GG-NER deficiency results in UV hypersensitivity.…”
Section: The Subpathways Of Nermentioning
confidence: 99%
“…It is likely that increased cell death in CS cells in response to UV light is not solely derived from disturbed cellular homeostasis because of a lack of vital transcripts, but that blocked transcription complexes are very cytotoxic structures, which induce a strong damage or persistent signaling cascade. Next to its vital role in protecting cells against a DDR that is too strong (apoptosis or permanent cell-cycle arrest), TC-NER seems also important in preventing UV-induced transcription-associated mutagenesis (Hendriks et al 2010;Schärer 2013).…”
Section: Nucleotide Excision Repair and Its Coupling To Transcriptionmentioning
confidence: 99%
“…The NER pathway is responsible for excising and repairing CBPD mutations after UVR, and it is a necessary mechanism that is used to repair a wide range of DNA lesions (14). NER can be categorized into two subpathways: global genome repair (GGR) and transcription-coupled repair (15,16).…”
mentioning
confidence: 99%
“…For this we extended our analysis to a mutant affecting CENTRIN2 (CEN2), which is part of the XPC complex (Xeroderma pigmentosum, complementation group C) that recognizes bulky DNA adducts, 7,8 and to a mutant affecting RAD10, which is an endonuclease involved in the dual excision of photoproducts. 1 Using the methylation-dependent restriction enzyme, McrBC, coupled to qPCR, we found that both cen2 and rad10 mutant plants exhibit DNA methylation alterations similar to those observed in several previously identified ddb2-induced Differentially Methylated Regions 6 (DMRs; Fig. 1).…”
mentioning
confidence: 94%
“…DNA DAMAGE-BINDING PROTEIN 2 (DDB2) is the main factor involved in the recognition of UV-induced DNA lesions during Global Genome Repair (GGR) in mammals and in plants. 1 In a recent study we reported that, in Arabidopsis, loss of DDB2 function alters DNA methylation patterns at many repeat loci and protein coding genes. We demonstrated that DDB2 acts in a complex with ARGONAUTE 4 (AGO4) to control de novo DNA methylation via the modulation of the local abundance of 24-nt small interfering RNAs (siRNAs).…”
Section: Introductionmentioning
confidence: 99%